Penyuluhan Perawatan Bayi Baru Lahir pada Ibu Prenatal dan Post Partum di Ruang Nifas dan Poli Kebidanan RSUD Arjawinangun Kabupaten Cirebon - Nengsih Yulianingsih; Indra Ruswadi; Priyanto Priyanto (Jurnal Pengabdian Bidang Kesehatan, 2024)
The maternal and child mortality rate in Indonesia is still quite high, where one of the main causes of death is in the neonatal period. The postpartum mother is one of the people closest to the newborn and who must take care of the baby's health. This community service activity is carried out in the form of educational activities or health counseling regarding newborn health care for prenatal and postpartum mothers at Arjawinangun Hospital, Cirebon Regency, with the provision of lies and direct counseling for the effectiveness of activities. Based on the health counseling activity, it was found that there was an increase in the knowledge of prenatal and postpartum mothers about newborn health care after the activity was carried out. The follow-up plan for the implementation of this activity will be carried out in collaboration with the Health Center to carry out assistance in the practice of newborn health care for newborn mothers. Conclusion: there is an increase in prenatal and postpartum maternal knowledge about newborn care.